2022
DOI: 10.3390/ijms23031835
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as the Cornerstone of Neuroimmunoendocrinology

Abstract: Much attention has been recently drawn to studying melatonin – a hormone whose synthesis was first found in the epiphysis (pineal gland). This interest can be due to discovering the role of melatonin in numerous physiological processes. It was the discovery of melatonin synthesis in endocrine organs (pineal gland), neural structures (Purkinje cells in the cerebellum, retinal photoreceptors), and immunocompetent cells (T lymphocytes, NK cells, mast cells) that triggered the evolution of new approaches to the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 172 publications
(213 reference statements)
0
17
0
2
Order By: Relevance
“…Melatonin (N-acetyl-5-methoxytryptamine, C 13 H 16 N 2 O 2 ), a kind of neuroendocrine hormone, is mainly synthesized and secreted by the pineal gland of brains and exerts effects via its membrane receptors (MT1 and MT2) [ 20 , 21 ]. Melatonin is also synthesized in respiratory epithelia and bone marrow cells as well as macrophages [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin (N-acetyl-5-methoxytryptamine, C 13 H 16 N 2 O 2 ), a kind of neuroendocrine hormone, is mainly synthesized and secreted by the pineal gland of brains and exerts effects via its membrane receptors (MT1 and MT2) [ 20 , 21 ]. Melatonin is also synthesized in respiratory epithelia and bone marrow cells as well as macrophages [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin is also synthesized in respiratory epithelia and bone marrow cells as well as macrophages [ 22 , 23 ]. It is widely recognized that melatonin is in charge of regulating sleep and circadian rhythm and also plays important roles in anti-inflammation and antioxidation [ 20 ]. Recent evidence indicated that melatonin had potential abilities of antivirus infection, including respiratory syncytial virus (RSV), influenza virus, and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its pro-inflammatory properties have been well-documented in several studies of leukocyte-derived cell lines; therefore, melatonin may be detrimental in autoimmune diseases ( 215 ), rheumatoid arthritis ( 268 ), and multiple sclerosis ( 269 ). The immune effects of melatonin are condition-based, although the conditions are not fully understood ( 270 , 271 ). Melatonin exhibits pro-oxidant, pro-apoptotic, and SIRT1-downregulating properties in cancer cells.…”
Section: Potential Adverse Effects Of Melatonin In the Elderlymentioning
confidence: 99%
“…Melatonin (N-acetyl-5-methoxy-tryptamine) is a hormone primarily synthesized by the epiphysis (pineal gland) from L-tryptophan through enzymatic cascade reactions, following a circadian rhythm (59). Apart from epiphysis, melatonin synthesis was reported in other endocrine organs, neural structures, and immunocompetent cells (60). Beyond chronobiology functions, melatonin exerts antioxidant, antiproliferative, antiinflammatory, immunomodulatory, metabolic, and other beneficial effects (61).…”
Section: Melatoninmentioning
confidence: 99%